GsEXPA8 Enhances Soybean Tolerance of NaHCO3 Stress by Regulating Root Morphology - Mengyu Liu; Jixiang Tang; Shengjie Ma; Yujing Liu; Xiaoyu Wang; Xinlei Du; Xiaohuan Sun; Yucheng Zeng; Yulong Zeng; Xiaodong Ding; Yingpeng Han; Junfeng Zhang; et al. (Agronomy)
Saline–alkali environments restrict soybean production in China. Wild soybean genes can be used to improve the alkaline tolerance of cultivated soybean in molecular breeding. The expansin protein family promotes cell wall expansion. In this study, the relative expression levels of expansin family genes in wild soybean treated with 50 mM NaHCO3 were measured at 0, 3, 6, and 12 h, and the relative expression of GsEXPA8 was found to be higher at 12 h. Wild soybean was treated with abscisic acid (ABA), indole-3-acetic acid (IAA), gibberellic acid (GA), and jasmonic acid (JA), and GsEXPA8 was found to respond to ABA and IAA signals. Sequence analysis shows that GsEXPA8 has DPBB_EXPA and expansin domains. Subcellular localization analysis shows that GsEXPA8 was localized in the cytoplasm in protoplasts and the cell membrane or wall in tobacco, indicating that it has nuclear membrane localization signals. GsEXPA8 overexpression reduced the malondialdehyde content in transgenic plants treated with NaHCO3 and increased peroxidase activity before treatment. After the transformation of soybean roots from hair roots, GsEXPA8 was found to be expressed in the outer root cells and promote the development of thicker, shorter roots, thereby improving the plant’s alkaline tolerance. Stable GsEXPA8 transformation improved saline alkaline tolerance via the regulation of the alkali stress-related genes GmKIN1, GmRD22, GmDnaJA6, GmNFYC1, and GmMYB14. These findings provide support for further research on alkali-tolerance regulation pathways and molecular breeding for alkali tolerance.